Synthesis of cyclobutane-containing tricyclic β-lactams based on a saturated scaffold enabled by iron-catalysed (2 + 2)-cycloaddition - Freitag, Lea; Zeh, Johannes; Ziegenhagen, Levi A.; Becker, Felix J.; Roşca, Dragoş-Adrian (Chemistry - a European journal, 2025)
Highly saturated, three-dimensional β-lactams are valuable motifs in medicinal chemistry, yet general routes to cyclobutane-fused analogues remain scarce. Here we disclose a concise strategy that delivers pyrrolidine-, piperidine-, and azepane-based tricyclic β-lactams. A pyrimidinediimine-iron catalyst first constructs the cyclobutane ring and the N-heterocycle in one step through an intermolecular [2 + 2]-cycloaddition of allyl amines; a subsequent photochemical intramolecular C─H insertion then forges the β-lactam. The major products adopt rigid, cage-like conformations confirmed for the pyrrolidine series by single-crystal X-ray diffraction. Comprehensive conformer sampling (using CREST), DFT-calculated NMR shifts, and DP4 statistical analysis establish the stereochemistry across the library. Strain-release opening of the β-lactam ring furnishes methylphenidate analogues in a single step, underscoring the scaffolds’ synthetic versatility. Comparative studies on the corresponding bicyclic systems highlight the unique three-dimensionality imparted by the additional cyclobutane ring, further expanding the toolbox for lead-oriented synthesis.
Im Titel steht der Ausdruck "2 + 2" in eckiger Klammer
Online veröffentlicht am 26. September 2026
Gesehen am 20.01.2026